2018
DOI: 10.1016/j.jana.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

PrEParing Women to Prevent HIV: An Integrated Theoretical Framework to PrEP Black Women in the United States

Abstract: Preexposure prophylaxis (PrEP) with optimal adherence has demonstrated efficacy in reducing HIV incidence in women. Black women are disproportionately burdened by the HIV epidemic, accounting for more than half of all new HIV cases in women, thereby making PrEP an ideal prevention strategy for this group. However, to date, PrEP uptake by women in the United States has been slow. Further domestic research is needed to understand the multilevel factors related to PrEP awareness, uptake, and implementation in Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 50 publications
4
27
1
2
Order By: Relevance
“…Furthermore, barriers that prevent uptake are not universal, and can be population-specific, exacerbated by co-prevalent syndemic conditions such as racism, homophobia, poverty, inadequate education, and behavioral health issues. The findings presented here have also been identified by others, who have noted similar common barriers overall [102][103][104] and in population groups at highest risk [105][106][107][108][109][110][111][112].…”
Section: Potential Solutions To Barrierssupporting
confidence: 89%
“…Furthermore, barriers that prevent uptake are not universal, and can be population-specific, exacerbated by co-prevalent syndemic conditions such as racism, homophobia, poverty, inadequate education, and behavioral health issues. The findings presented here have also been identified by others, who have noted similar common barriers overall [102][103][104] and in population groups at highest risk [105][106][107][108][109][110][111][112].…”
Section: Potential Solutions To Barrierssupporting
confidence: 89%
“…pill). (14,26,27,45) In addition, we determined that our education intervention was feasible and acceptable in both modalities (online and in-person). Though, the in-person vehicle for intervention delivery was more positively received relative to online delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to disproportionate HIV rates among Black women, especially in geographic areas with a high HIV prevalence, they are important priority populations to inform about PrEP. However, limited data exist from PrEP investigations that focus on women, especially Black women living in the U.S (12,14,(25)(26)(27). Generally, women reported that: a) they were unaware of PrEP --and angry about not knowing or being taught-but found the option attractive; b) they would be likely to seek information about PrEP from their Obstetricians, Primary Care Providers, or Community-based Organizations, Media, schools, peer-to-peer/friend-to-friend; and c) PrEP was seen as additional, not substitute, protection to condoms (14).…”
Section: Focus Populations and Prep As Hiv Preventionmentioning
confidence: 99%
“…Terapi dan pengobatan pada penyakit HIV memerlukan proses yang lama, sehinga pasien harus rajin untuk kontrol (Chenneville, Machacek, St. John Walsh, Emmanuel, & Rodriguez, 2017). Namun di Indonesia masih banyak pasien yang tidak kembali kontrol dalam waktu minimal 3 bulan bahkan lebih secara terus menerus (lost to follow up) yang dapat berdampak pada proses pengobatan pasien dan monitoring tenaga kesehatan terhadap pasien dengan HIV AIDS (Chapman Lambert, Marrazzo, Amico, Mugavero, & Elopre, 2018).…”
Section: Pendahuluanunclassified
“…Sama hal hanya dengan hasil penelitian tentang perceived benefit yang juga responden menganggap bahwa manfaat dari obat ARV kurang memberikan manfaat besar. Namun dalam hal ini perilaku lost to follow-up yang baik dapat disebabkan karena dukungan dari keluarga yang besar sehingga responden tidak melakukan lost to follow up dan menjalani pengobatan dengan obat ARV (Chapman Lambert et al, 2018).…”
unclassified